The Application of the Res Ipsa Loquitur Doctrine as a Principle of Evidence in Medical Malpractice - Firman Floranta Adonara; Y.A. Triana Ohoiwutun; Vicko Taniady (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
This paper aims to discuss the doctrine of res ipsa loquitur as an unlawful act in medical malpractice and its implications on the balance of protection for patients and medical personnel after the enactment of the Health Law. The urgency of this paper lies in examining the applicability of the res ipsa loquitur doctrine in relation to Articles 310 and 440 of the Health Law. The application of the res ipsa loquitur doctrine in proving medical malpractice cases is strategic in determining the existence or absence of unlawful acts due to negligence. The res ipsa loquitur doctrine makes it easier for patients as plaintiffs to prove negligence through a reverse burden of proof mechanism by medical personnel. Although not a formal piece of evidence, the res ipsa loquitur doctrine can be used as a relevant legal basis, especially when supported by medical records, to assess the conformity of medical actions with professional standards and operational procedures. The legal relationship in therapeutic transactions, which is asymmetrical in nature, requires proportional protection, both in relation to the provisions of Article 310 of the Health Law, which encourages non-litigation dispute resolution, and in relation to Article 440, which opens up criminal law channels for serious negligence in medical services. Therefore, the application of the res ipsa loquitur doctrine in criminal law must be strictly limited through a restorative justice approach as a fair alternative with balanced protection interests for patients and medical personnel.